Taxonomy of Trauma Leadership Skills: A Framework for Leadership Training and Assessment. (February 2016) - Leenstra, Nico F.; Jung, Oliver C.; Johnson, Addie; Wendt, Klaus W.; Tulleken, Jaap E.
Abstract : Purpose: Good leadership is essential for optimal trauma team performance, and targeted training of leadership skills is necessary to achieve such leadership proficiency. To address the need for a taxonomy of leadership skills that specifies the skill components to be learned and the behaviors by which they can be assessed across the five phases of trauma care, the authors developed the Taxonomy of Trauma Leadership Skills (TTLS). Method: Critical incident interviews were conducted with trauma team leaders and members from different specialties—emergency physicians, trauma surgeons, anesthesiologists, and emergency ward nurses—at three teaching hospitals in the Netherlands during January–June 2013. Data were iteratively analyzed for examples of excellent leadership skills at each phase of trauma care. Using the grounded theory approach, elements of excellent leadership skills were identified and classified. Elements and behavioral markers were sorted and categorized using multiple raters. In a two-round verification process in late 2013, the taxonomy was reviewed and rated by trauma team leaders and members from the multiple specialties for its coverage of essential items. Results: Data were gathered from 28 interviews and 14 raters. The TTLS details 5 skill categories (information coordination, decision making, action coordination, communication management, and coaching and team development) and 37 skill elements. The skill elements are captured by 67 behavioral markers. The three-level taxonomy is presented according to five phases of trauma care. Conclusions: The TTLS provides a framework for teaching, learning, and assessing team leadership skills in trauma care and other complex, acute care situations. Abstract : Supplemental Digital Content is available in the text.